Euglycemic ketoacidosis complicating empagliflozin therapy in a Bangladeshi type 2 diabetic lady (BIRDEM Medical Journal, 2021)
Diabetic ketoacidosis (DKA) is an acute complication of diabetes mellitus, which may occurin both type 1 and type 2 diabetic patients. It is characterized by hyperglycaemia [blood glucose levels > 250 mg/dL (13.8 mmol/ L)], metabolic acidosis (pH